Do sentido ao problema da verdade na fenomenologia de Edmund Husserl: implicações da ressignificação transcendental do conceito de transcendência na adaequatio rei et intellectus husserliana - Rocha, João Marcelo Silva da (2024)
The present thesis develops reflections on the concepts of truth and transcendence as they manifest especially in the Phenomenology of Edmund Husserl, with the general aim of analyzing the implications of the meaning of “transcendence” in the correspondence-based conception of truth prevalent in Husserlian thought. Structured in five chapters, the investigation begins by outlining the traditional sense of truth as correspondence in its structuring aspects and the emerging problematic in the configuration of the relationship between knowing subject and knowable object based on specific delimitations of the concept of transcendence. Thus, Husserl's concepts of “truth” and “evidence” advocated in the Logical Investigations are analyzed, delineating the four phenomenological senses of “truth” as exposed in §39 of the 6th Logical Investigation. Moreover, it is emphasized the primacy of the meaning of “true being” in determining the other senses of truth. The third chapter explores the senses of “transcendence” and “immanence”, examining the redefinition of these concepts promoted with the transition to Transcendental Phenomenology and how it reconfigures the relationship between subjectivity and objectivity, revealing the former as constitutive and the latter as constituted. This transformation suggests the loss of the autonomy of the transcendent in relation to subjectivity, a presupposition of correspondence-based truth. In the fourth chapter, a similar approach is taken to that in the second chapter, focusing, however, on Husserl's description of the senses of “truth” and “evidence” in works of the transcendental phase of Phenomenology. The aim of this analysis is to demonstrate that the formal characterization of such concepts remains in accordance with the parameters established in the Logical Investigations, contrary to what the transformations discussed in the third chapter might suggest, and that the primacy of the meaning of “truth” attributed to the object also persists in the transcendental version of Husserlian thought. Considering this, the problem regarding the implications of “transcendence” in Husserl's conception of truth is established in the fifth and final chapter: initially, it is explained how correspondence-based truth becomes problematic in the Logical Investigations precisely due to the meaning of “transcendent” adopted in this work. Finally, a justification is proposed for maintaining correspondence-based truth in Transcendental Phenomenology due to the implications of the specifically phenomenologicaltranscendental concept of transcendence. This interpretative proposal is presented through the demarcation of a double constitutive layer concerning the objective pole of the intentional relation committed to the achievement of true knowledge. Based on the description of the constitutive processes carried out in each of these layers, it is ultimately argued that the autonomy of the transcendent in relation to the veritative relation – a requirement inscribed in the correspondence-based conception of truth – is ensured by the constitution of the transcendent as such, carried out in the foundational layer. Besides, the constitutive dependence of the transcendent as true in relation to subjectivity, imposed by transcendental reduction, is expressed in the synthesis of evident fulfillment carried out in the founded layer.